Components for Simulation of piezoelectrically actuated Systems with SyMSpace. Issue 15 (2019) - Reischl, Daniel; Meindlhumer, Martin; Trinkl, Martin; Pechstein, Astrid; Silber, Siegfried
Abstract: The concept of automating the computation steps in a design process along different simulation tools leads to a more efficient use of knowledge and computational resources. In this paper the software tool SyMSpace, which realizes this automatization, and the available components concerning the simulation of piezoelectrically actuated systems is presented. The finite element model of a circular piezoelectric patch on a rectangular aluminium substrate using novel mixed finite elements is used as an example to show how to create a well-documented and easy-to-use component. Tangential displacements and normal normal stresses (TDNNS) are used as mechanical degrees of freedom and the finite elements are readily available in open source software package Netgen/NGSolve. In order to simplify the installation and usage of specialized (open source) software tools and help to reproduce results in scientific publications, the concept of (docker) containers is integrated in SyMSpace.